A study on fuel additive of methanol for room temperature direct methanol fuel cells - Wang, Meng; Chen, Ming; Yang, Zhaoyi; Wang, Yituo; Wang, Yingrui; Liu, Guicheng; Lee, Joong Kee; Wang, Xindong (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Hydrogen peroxide is added into the anode methanol fuel as a pro-oxygenic agent to improve the electro-oxidation reaction rate of methanol in low-temperature direct methanol fuel cell. Cyclic voltammetry, electrochemical impedance spectroscopy and steady-state polarization with three-electrode system are used to test the catalytic efficiency with different concentrations of hydrogen peroxide additive. The mechanism of pro-oxygenic activity is revealed by cyclic voltammetry method. The results of electrochemical analysis show that the peak current density and peak power density are the highest when the concentration of hydrogen peroxide additive is 0.1 M at room temperature, increase 12.2% and 34.1% than those of pure methanol solution, respectively. The anode charge transfer resistances reduce gradually as the concentrations of hydrogen peroxide increase from 0 to 0.3 M. The tests under different temperature indicate that the promotion effect of hydrogen peroxide additive is significant at room temperature rather than at high temperature. The results show that hydrogen peroxide can be an effective pro-oxygenic agent for methanol electro-oxidation to improve the anode methanol electro-oxidation reaction of direct methanol fuel cell at room temperature.